MANAJEMEN PENGELOLAAN BADAN USAHA MILIK DESA (Studi Di Desa Watulaney Amian Kecamatan Lembean Timur Kabupaten Minahasa) - KOSO, JELI; OGOTAN, MARTHA; MAMBO, RULLY (Sam Ratulangi University, 2018)
Abstract: In an effort to improve the welfare of the community, the Government through the CommunityEmpowerment and Village Development Agency to establish a financial institution that is BUMDes is afinancial institution whose purpose is to run a business and improve the economy of the community. VillageOwned Enterprises (BUMDes) are managed by the community and village government in an effort tostrengthen the village economy and are shaped based on village needs and potentials. The purpose of thisresearch is to know how Management of Village Owned Enterprise in Watulaney Amian Village, EastLembean Sub-district of Minahasa Regency. The research method used in this research is qualitativemethod. Informants in the study are people who can provide information about the situation and conditionof the research background. The focus of research is seen from indicators according to George Terry,namely planning, organizing, mobilization and supervision. Technique of collecting data throughobservation / direct observation research, do interview, and documentation. The results showed thatManagement of Village Owned Enterprise in Watulaney Amian Village, East Lembean District, MinahasaRegency has not been done well. At the stage of planning has not implemented the program that has beenin the planning and implementation of the manager has not been maximized due to lack of organizationalstewardship to be the cause of not implemented impeccable management.Keywords : Management , Village Owned Enterprise (BUMDes)